THE IMPACT OF COMPENSATION AND WORK ENVIRONMENT ON THE PERFORMANCE OF PT AJA MEGA PERKASA EMPLOYEES THROUGH MOTIVATION - Ahmad Sirri; Eka Febriani; Lewi Patabang (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2024)
PT AJA MEGA PERKASA is an agency running withinside the mining zone withinside the metropolis of Samarinda, that's one of the business sectors that has made a big contribution to Indonesia, beginning from growing export revenues, local development, growing financial activity, starting employment possibilities and reassets of profits for the imperative and local budgets. In this research, descriptive quantitative methods were used. The research object of PT Aja Mega Perkasa is the workshop and office section. This research uses non-probability sampling. The sample included 60 people. The data collection method was carried out through the distribution of questionnaires. The results of the tests conducted showed that (1) compensation has a large positive impact on motivation, (2) work environment has a large positive impact on motivation, and (3) motivation has a large positive impact on motivational performance. I realized that I should give. (4) Compensation has a positive and significant impact on employee performance through motivation. (5) Work environment has a positive and significant impact on employee performance through motivation. Keywords: Compensation, Work Environment, Motivation, Employee Performance